HPV vaccine recommendations by age: A survey of providers in federally qualified health centers. Issue 1 (31st December 2023) - Lake, Paige; Fuzzell, Lindsay; Brownstein, Naomi C.; Fontenot, Holly B.; Michel, Alexandra; McIntyre, McKenzie; Whitmer, Ashley; Rossi, Sarah L.; Perkins, Rebecca B.; Vadaparampil, Susan T.
ABSTRACT: Clinician recommendation remains a critical factor in improving HPV vaccine uptake. Clinicians practicing in federally qualified health centers were surveyed between October 2021 and July 2022. Clinicians were asked how they recommended HPV vaccination for patients aged 9–10, 11–12, 13–18, 19–26, and 27–45 y (strongly recommend, offer but do not recommend strongly, discuss only if the patient initiates the conversation, or recommend against). Descriptive statistics were assessed, and exact binomial logistic regression analyses were utilized to examine factors associated with HPV vaccination recommendation in 9–10-y-old patients. Respondents (n = 148) were primarily female (85%), between the ages of 30–39 (38%), white, non-Hispanic (62%), advanced practice providers (55%), family medicine specialty (70%), and practicing in the Northeast (63%). Strong recommendations for HPV vaccination varied by age: 65% strongly recommended for ages 9–10, 94% for ages 11–12, 96% for ages 13–18, 82% for age 19–26, and 26% for ages 27–45 y. Compared to Women's Health/OBGYN specialty, family medicine clinicians were less likely to recommend HPV vaccination at ages 9–10 ( p  = .03). Approximately two-thirds of clinicians practicing in federally qualified health centers or safety net settings strongly recommend HPV vaccine series initiation at ages 9–10. Additional research is needed to improve recommendations in younger age groups.